Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar Tematik Terpadu Kelas V SD - Muluk, Alfaroji; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The research is motivated by the lack of optimal planning and implementation of integrated thematic learning processes which include: 1) Teachers are not optimal in designing learning implementation plans, 2) Teachers do not use models in high class learning, 3) Teachers do not involve students in group learning, lack of sharpening student skills in making work and impacting student learning outcomes, 4) Teachers are more dominant in the learning process so learning becomes conventional and boring for students. The purpose of this study is to describe the Application of Project Based Learning Models to Improve Student Learning Outcomes in Thematic Integrated Learning in Class V SDN 34 Simpang Haru, Padang City.This type of research is a classroom action research consisting of 2 cycles, carried out in 4 stages, namely planning, implementing, observing, and reflecting using qualitative and quantitative approaches. This research technique is observation and test. This research data in the form of information about the implementation process obtained from the observation of lesson plans, teacher aspects, and aspects of students and learning outcomes. The subjects of the study were the 25th grade teachers and students of SDN 34 Simpang Haru.The results showed planning, implementation and learning outcomes have increased. The assessment shows that RPP I cycle 90.28%, 94.4% second cycle. The activities of teachers and students in cycle I 89.06% (B), cycle II 93.75% (SB). The attitude aspect increased from cycle 1 to cycle 2 ie students reflected the main values of religious character, independence and integrity. Knowledge aspects of the first cycle of Indonesian Language 70 (B-) and Natural Sciences 74.9 (B), the second cycle of Indonesian Language 89.28 (A) and Natural Sciences 81.96 (A-). Aspects of Indonesian Language Cycle I 68.8 (B-) and Natural Sciences 74.5 (B), Indonesian Cycle II 95 (A) and Natural Sciences 95 (A). Research by applying the project based learning model improves the thematic learning outcomes of students in grade V of elementary school.